MATHEMATICAL MODELING OF TRANSITION HEAT AND HYDRAULIC PROCESSES IN THE WATER TUBE HEATING SYSTEM WITH RADIATOR THERMOSTATS - Kutnyi, B. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The modern building normative base Ukraine provides installation radiator thermostat on heating devices water heating systems. In spite of the declared producers energy-efficient effect in 10 – 20% of the annual cost of heat and comparatively not high cost, the energy saving measure is not widely spread in Ukraine. It is related to number of peculiarities of domestic of systems heating: use of hydraulic elevator thermal units, a small number of buildings equipped with heat counters, the constant hydraulic regime of systems heating and district heating, etc. This work is devoted to investigation of thermal and hydraulic regimes of tube heating systems with thermostatic controls. For the simulation transient thermal and hydraulic regimes of heating systems with radiator thermostats in this paper proposed of the mathematical model. Its peculiarity is a comprehensive consideration of various factors (both disturbing and regulating) on the thermal and hydraulic modes of work automated heating system. This mathematical model can be used to create computer programs and perform a variety of researches in the field automatic control thermal mode of premises. The research results can be applied to the design and optimization of modern control systems tempering heat. Keywords: mathematical model, heating system, thermostatic valve.